Young children's agency: exploring children's interactions with practitioners and ancillary staff members in Greek early childhood education and care settings. Issue 7 (3rd July 2018) - Katsiada, Eleni; Roufidou, Irini; Wainwright, Jonathan; Angeli, Varvara
ABSTRACT: Most research in early childhood education and care (ECEC) settings, in Greece and internationally, focuses on children's relationships with their early years practitioners, but evidence regarding young children's role in the formation of these relationships is limited. This paper focuses on 10 children, under the age of three, recognizing children's agency and their significant contribution to the formation of interpersonal relationships with practitioners and ancillary staff members. The paper draws on findings from an ethnographic case study, conducted in two Greek day-care settings over the course of six months, which used an adaptation of the Mosaic Approach. The analysis suggests that children's relationships with significant adults beyond the home are paramount for children and influence and shape the way they perceive and experience the settings.